CURRICULUM TRANSFORMATION USING ICT IN THE TEACHING PHYSICAL EDUCATION IN SECONDARY SCHOOLS IN ONITSHA L.G.A. OF ANAMBRA STATE - Dike, D.O; Chukwurah, Linda N. (International Journal of Human Kinetics, Health and Education, 2023)
The study was to investigate curriculum transformation and the use of ICT in teaching physical education in secondary schools in Onitsha L .G.A of Anambra State. Descriptive survey research design was used and the population consisted of all the physical education teachers in all the 30 secondary schools in the L.G.A, hence, no sampling. Researchers made questionnaire were used for data collection and research questions were answered using mean scores. 2.50 was set as the criterion mean in the study. The results revealed the following: Use of ICT in teaching P.E improve students’ skills and techniques; Assist students in the review and evaluation of their performance; Develop student’s knowledge and understanding of the subject; and Develop student’s understanding of the human body and health. Based on the results, the researchers recommended that Ministry of Education should map out ways to ensure that teachers integrate ICT in teaching of physical education.